Kepuasan Konsumen Waroeng Steak Jatiwaringin yang dipengaruhi Persepsi Harga, Promosi, dan Lokasi - Kezia Naftali Gerungan; Aris Budiono (Jurnal Riset Akuntansi, 2023)
This journal has been reviewed to conduct research in order to be able to analyze the influence of independent variables, that is Price Perception (X1), Promotion (X2), and Location (X3) which are related to the dependent variable, that is Customer Satisfaction (Y). Through the quantitative method used with multiple linear regression using the SPSS application. In this research, 100 respondents were obtained using the Likert scale method, to be able to understand the simultaneous and partial effects. It can be seen from the results that the three independent variables can influence the dependent variable simultaneously, and partially all independent variables can affect the dependent variable both price perception on consumer satisfaction, promotion on customer satisfaction, and location on customer satisfaction.